2014
DOI: 10.3390/insects5030689
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Aggression in Giant Honey Bees (Apis dorsata)

Abstract: We investigated intraspecific aggression in experimental nests (expN1, expN2) of the giant honey bee Apis dorsata in Chitwan (Nepal), focusing on interactions between surface bees and two other groups of bees approaching the nest: (1) homing “nestmate” foragers landing on the bee curtain remained unmolested by guards; and (2) supposed “non-nestmate” bees, which were identified by their erratic flight patterns in front of the nest, such as hovering or sideways scanning and splaying their legs from their body, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 62 publications
4
9
0
Order By: Relevance
“…In contrast, Starr et al (1987) reported that A. d. dorsata tend to built a nest in an open air location and clean by liane plants. Weihmann et al (2014) also reported that A. d. dorsata tends to built nests on open so that the circumstances are more easily seen by predators, such as wasp Polistes olivaceus. The weaker colony defense caused the higher risk of larvae and colonies attacked by disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, Starr et al (1987) reported that A. d. dorsata tend to built a nest in an open air location and clean by liane plants. Weihmann et al (2014) also reported that A. d. dorsata tends to built nests on open so that the circumstances are more easily seen by predators, such as wasp Polistes olivaceus. The weaker colony defense caused the higher risk of larvae and colonies attacked by disease.…”
Section: Discussionmentioning
confidence: 98%
“…Kahono et al (1999) also reported that nests of A. dorsata were found in a height less than 10 meter from ground surface over a period of two years. While, Weihmann et al (2014) reported that A. dorsata prefer high trees to make their nests. Previous studies reported that A. dorsata tend to prefer places with a height of more than 10 meters to built nests (Starr et al 1987;Kahono et al 1999;Hadisoesilo 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A. dorsata are relatively docile towards conspecifics, but they do become more defensive towards non-nestmates during the migratory season when a new nest has settled in their vicinity. Actual robbing is still rarely observed [42]. Interestingly, managed A. mellifera colonies kept at a similar density show a drift rate that is 35-fold higher.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 97%
“…However, a very low frequency of drifted workers (0–6.25%) has been reported in aggregations [ 12 , 13 ] suggesting an elaborate nestmate recognition system. Initially colonies respond to visual cues like irregular flight maneuvers of non-nestmates with shimmering behavior [ 14 ], whereas in close-range interactions after landing on the curtain olfactory cues like CHC profile differences are more likely used to identify the non-nestmate.…”
Section: Introductionmentioning
confidence: 99%